2018
DOI: 10.1016/j.pneurobio.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor γ (PPARγ): A master gatekeeper in CNS injury and repair

Abstract: Peroxisome proliferator-activated receptor γ (PPARγ) is a widely expressed ligand-modulated transcription factor that governs the expression of genes involved in inflammation, redox equilibrium, trophic factor production, insulin sensitivity, and the metabolism of lipids and glucose. Synthetic PPARγ agonists (e.g. thiazolidinediones) are used to treat Type II diabetes and have the potential to limit the risk of developing brain injuries such as stroke by mitigating the influence of comorbidities. If brain inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
156
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(160 citation statements)
references
References 503 publications
(610 reference statements)
3
156
0
1
Order By: Relevance
“…In this study, we found a significant decrease in PPARγ DNA-binding activity in a perilesion cortex, as well as mRNA expression of PPARγ-targeted downstream genes in cerebral microvascular fragment at one day after stroke in T2DM mice, but it was significantly elevated by the poststroke administration of rFGF21. Although, as a transcriptional factor, how the rFGF21-activated PPARγ regulates subesequent signaling pathways in modulating junction protein expression and preserving BBB integrity remains to be elucidated, accumulating experimental evidence has supported the critical roles of PPARγ activity in not only BBB protection, but also improvement of cellular survival and recovery of homeostatic equilibrium after ischemic stroke [12]. It is possible that other molecular mechanisms may be also involved in poststroke BBB protection by rFGF21, which needs to be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found a significant decrease in PPARγ DNA-binding activity in a perilesion cortex, as well as mRNA expression of PPARγ-targeted downstream genes in cerebral microvascular fragment at one day after stroke in T2DM mice, but it was significantly elevated by the poststroke administration of rFGF21. Although, as a transcriptional factor, how the rFGF21-activated PPARγ regulates subesequent signaling pathways in modulating junction protein expression and preserving BBB integrity remains to be elucidated, accumulating experimental evidence has supported the critical roles of PPARγ activity in not only BBB protection, but also improvement of cellular survival and recovery of homeostatic equilibrium after ischemic stroke [12]. It is possible that other molecular mechanisms may be also involved in poststroke BBB protection by rFGF21, which needs to be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously proposed a disease-modifying approach using recombinant fibroblast growth factor 21 (rFGF21) to treat ischemic stroke mice with T2DM and observed the beneficial effects of rFGF21 on long-term neurological outcomes in T2DM stroke mice [10]. Very interestingly, FGF21 has been reported as a key mediator involving in the physiological and pharmacological actions of peroxisome proliferator-activated receptor gamma (PPARγ) [11], which is an important nucleus receptor that transcriptionally regulates multiple gene expressions and functions as a master gatekeeper for cytoprotective stress response, such as anti-inflammation and antioxidative stress, in poststroke brain injury and repair [12]. Our previous study showed that rFGF21 administration increases PPARγ DNA-binding activity three days after stroke in the perilesion cortex of T2DM mice, which might be partially responsible for the reduction of brain tissue damage and detrimental proinflammatory cytokine expressions [10].…”
Section: Introductionmentioning
confidence: 99%
“…As a widely used antidiabetic drug which works as an insulin sensitizer by binding to the PPAR‐γ in fat cells, RSG may also serve as a master gatekeeper in CNS injury and repair . It is emerging that the PPAR‐γ is constitutively expressed in microglia and activating PPAR‐γ in microglia may regulate the phenotypic change of microglia .…”
Section: Discussionmentioning
confidence: 99%
“…As a widely used antidiabetic drug which works as an insulin sensitizer by binding to the PPAR-γ in fat cells, RSG may also serve as a master gatekeeper in CNS injury and repair. [37][38][39] It is emerging that the PPAR-γ is constitutively expressed in microglia and activating PPAR-γ in microglia may regulate the phenotypic change of microglia. [40][41][42][43] PPAR-γ activation could favor a reprogramming process of microglia toward a beneficial phenotype, with antiinflammatory and tissue-repair properties.…”
Section: Discussionmentioning
confidence: 99%
“…These neuroprotective effects are dependent on the activation of RXR/PPARγ (peroxisome proliferator-activated receptor γ) (Certo et al, 2015). PPAR controls the cells cytoprotective stress responses and can aid in the restoration of cellular homeostasis, hence promotion may improve the chances of cell survival (Cai et al, 2018). Rosiglitazone, an agonist of PPARγ, also has been found to have a neuroprotective effect through the inhibition of apoptosis and autophagy.…”
Section: Bexarotene and Rosiglitazonementioning
confidence: 99%